Fabrication and Characterization of Electrospun Nanofibrous Composite Membrane for Air Filtration (Journal of Fiber Bioengineering and Informatics, 2018)
One kind of composite membrane by combining electrospun nanofibrous membrane with fiberglass mesh was developed for air filtration. The fiber diameter, morphology of membranes, pressure drop and filtration efficiency of composite membrane were evaluated. The results revealed that the pressure drop and filtration efficiency of composite membrane decreased with the increase of winding speed (the higher winding speed is, the less of nanofibers are). The pressure drop of all samples at an airflow speed of 5 m/min was less than 25 Pa, which was much lower than the values from other reported work; and the highest filtration efficiency of sample in this work was more than 83% for particulate matters with 1.88 \u0016m.
Keywords: Electrospinning; Nanofiber; Light Transmittance; Pressure Drop; Filtration Efficiency.